Suspect until proven negative: dromopolitics and logics of surveillance in the Chinese people's war to stop the spread of COVID-19 - Vuori, Juha A; Gong, Jeremy (Oxford University Press (OUP), 2026)
The present article contributes to surveillance studies as well as health security studies by presenting an analysis of the Chinese COVID-19 dataveillance Track and Trace System (TTS) as a new form of dromopolitics. Unlike most states, China's total dataveillance combined with stringent means of discipline (strictest forms of quarantine) allowed China to retain societal flow-control that was akin to governmentality even without mass vaccination during the first year of the pandemic. In the TTS, colour was used as a technique with the goal of maintaining flow-control, for making the microscopic virus visible, and for providing a mundane security routine that provided visual tokens of trust and validity. Such measures worked to turn the uncontrollable terror of the virus into a manageable fear and were part of the emotional work done to maintain social stability and political legitimacy. We argue that Paul Virilio's notions of speed and dromopolitics provide for new insights into the politics of this unprecedented dataveillance operation. Our analytical reading in the article is based on previous literature on China's COVID-19 sociotechnical assemblages and first-hand experiences and observations in the PRC during its international closure.